Total synthesis of (+)-trans- dihydronarciclasine from (+)-7-azabicyclo[2.2.1]heptanone - Pandey, Ganesh; Fernandes, Rushil; Dey, Debasis; Majumder, Binoy (Tetrahedron, 2018)
A concise asymmetric total synthesis of Amaryllidaceae alkaloid (+)-trans-dihydronarciclasine is accomplished starting from optically pure 7-azabicyclo[2.2.1]heptanone scaffold in 13 linear steps. Key features of the strategy include substrate-directed stereoselective installation of the trans B-C ring junction and regioselective Wacker-type internal olefin oxidation to provide a rapid access to all hydroxyl functionalities over the key cyclohexane ring in a stereocontrolled manner. (C) 2018 Elsevier Ltd. All rights reserved.